2020
DOI: 10.1186/s12912-020-00468-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job satisfaction and turnover intention among nurses in Axum comprehensive and specialized hospital Tigray, Ethiopia

Abstract: Background: Nurses' turnover is a global concern which if not handled well can harm the productivity of an organization. The high turnover rate of health workers critically affects the health system, particularly in countries with limited resources. Hence, effective retention strategies require clear identification of the variables at the workplace that determines nurses' decision in staying in or leaving their employer organization. The aim of this study is to assess the relationship between job satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 38 publications
10
49
2
1
Order By: Relevance
“…The marriage rate in our study was 66.7%, and this agrees with similar studies that range from 64.0%–84.5% [ 24 , 28 31 ], but others reported low marriage rates, 39.3%–46.9% [ 2 , 7 , 22 , 25 ]. In our study, married nurse anesthetists had significantly higher JS than singles, unlike other reports which reported no significant difference [ 2 , 7 , 13 ] or non-satisfaction in the married group [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The marriage rate in our study was 66.7%, and this agrees with similar studies that range from 64.0%–84.5% [ 24 , 28 31 ], but others reported low marriage rates, 39.3%–46.9% [ 2 , 7 , 22 , 25 ]. In our study, married nurse anesthetists had significantly higher JS than singles, unlike other reports which reported no significant difference [ 2 , 7 , 13 ] or non-satisfaction in the married group [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Kinzl et al [ 29 ] reported absence of significant association between JS and variety of work, while Mahoney et al from the United States [ 4 ] reported skill variety and autonomy result in higher JS. We found that 80.3% of the nurse anesthetists were not satisfied with their pay which is higher than 36.5% reported by Gebregziabher et al [ 25 ].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The results from the SEM showed that factors related to the working environment significantly influenced factors of assured income regarding job attractiveness. Previous studies have also reported that turnover of healthcare professionals is caused by dissatisfaction with their work, but it is inferred that the factors causing dissatisfaction may differ depending on job content and educational background [ 16 , 20 ]. In particular, improvement in salary may improve the job satisfaction of dental hygienists in Japan.…”
Section: Discussionmentioning
confidence: 99%